FAKTOR-FAKTOR YANG MEMPENGARUHI PENERAPAN AKUNTANSI AKRUAL PADA PEMERINTAH KOTA PONTIANAK - Yani Riyani; Bob Mustafa; Linda Suherma (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2017)
This study aims to determine the extent of implementation of accrual accounting and the factors that influencethe level of implementation of accrual accounting in Pontianak. This research is a survey by means of collectingdata using questionnaires. The samples used were financial staff that makes the financial statements at 16 SKPD inPontianak. The analytical tool used is multiple regression analysis. The level of implementation is measured usingnine indicators adopted by the Government Accounting Standards based on Government Regulation No. 71 of2010 consists of revenue recognition (LO), Recognition load, Valuation and Presentation of Accounts Receivable,Recognition load inventory, assessment of fixed assets, depreciation of fixed assets, recognition of liabilities,Presentation of operational reports and presentation of changes in equity. The study found that the level ofimplementation of accrual accounting in Pontianak at 93.09%, and there are four factors that affect the applicationof accrual accounting in Pontianak is the level of education finance staff, the experience of running the cash to theaccrual accounting system, leadership and educational background the size of the labor force.Keyword : Cash Basis, Accrual Basis, Cash toward Accrual.